2015
DOI: 10.1016/j.apgeochem.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

A combined geochemical and isotopic study of the fluids discharged from the Montecatini thermal system (NW Tuscany, Italy)

Abstract: a b s t r a c tThe thermo-mineral fluids discharges of Montecatini Terme (Northern Apennines, Tuscany, Italy) have been exploited since the Roman times and despite the fact that this thermal complex is one of the biggest in Europe, the most recent geochemical investigations were published almost 40 years ago. To fill this gap, in this paper a detailed geochemical and isotopic investigation on the main thermal springs and wells from the Montecatini thermal system (MTS) is presented.The chemical and isotopic fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Indeed, in Northern Apennines, cold to hot Na-Cl and Ca-SO4 waters interacting with evaporites of the Burano Formation (Late Triassic) showed a mean Sr/ Ba weight ratio of 336 ± 210 (N = 45; Boschetti et al, 2005;Boschetti et al, 2017;Capecchiacci et al, 2015;unpublished data). The lower value outliers (Sr/ Ba \ 100) are mainly related to waters mixed with Ca-HCO3 and freshwaters interacting with Mesozoic limestones (Sr/Ba \ 10).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in Northern Apennines, cold to hot Na-Cl and Ca-SO4 waters interacting with evaporites of the Burano Formation (Late Triassic) showed a mean Sr/ Ba weight ratio of 336 ± 210 (N = 45; Boschetti et al, 2005;Boschetti et al, 2017;Capecchiacci et al, 2015;unpublished data). The lower value outliers (Sr/ Ba \ 100) are mainly related to waters mixed with Ca-HCO3 and freshwaters interacting with Mesozoic limestones (Sr/Ba \ 10).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the third group (G3) is characterized by groundwater with the highest concentrations of Li and Cs (S5, S11, S13, and S15) that suggests a different circulation model with respect to the other two groups. It is noteworthy that the samples of the second and third clusters are within or close to the ratios 1.2 < Rb/Cs < 3.0, typical of waters interacting with Upper Triassic Burano Formations [110][111][112], where the higher ratio is common of sulphate waters such as those from the Antrodoco area (S1, S2). In addition, the Li-Rb-Cs contents of the carbonatitic and silicate fractions of Cupaello rocks display red pentagons [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors [25], using stable isotopes of water, showed, for example, a predominant influence of Mediterranean air masses on the karst aquifer near the Slovenian-Italian border. They also observed how some types of water are influenced by water-rock interaction processes and meteoric water infiltrating at depth from the Triassic evaporite belonging to the Tuscan sedimentary series forming the surrounding reliefs (central Italy) [26]. In addition, stable isotopes of water have been used as inert tracers to indicate the residence time of groundwater in aquifer systems and potential sources of recharge [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%